Analyzing the Safeguarding Our Communities Act: Patch for Patch Return Policy in Ontario - Soo-Min Kim (McMaster University Library Press, 2018)
Fentanyl is prescribed to patients suffering from severe chronic pain. Transdermal patches are the best mode of delivery for patients who have developed tolerance for opioids. However, used patches still contain fentanyl that can be extracted and misused, with potentially severe consequences. To address this issue, patients who are prescribed fentanyl patches in Ontario are now required to return previously dispensed patches to receive new patches under the Safeguarding Our Communities Act: Patch for Patch (P4P) Return Policy. The problem is significant in Ontario because the province has the largest annual dispense rate of high-dose prescription fentanyl (112 units per 1,000 population) in Canada even though the prevalence rate of chronic pain is lower than the national reported range (16.6% in Ontario versus 19.6 to 21.9% in other provinces, according to Gomes et al. 2014). The primary goal of this reform is to instill responsible use of fentanyl patches, and to improve safety for patients and the public by having a central disposal process. The reform was modeled after a community initiative that was pioneered in North Bay after receiving great support from health professional colleges and communities that voluntarily integrated the program prior to the introduction of Bill 33. Preliminary data suggest that the P4P policy is positively received by health professionals, although ongoing evaluation is needed to assess the effectiveness of the policy in reducing misuse and abuse of prescribed fentanyl patches. Le fentanyl est prescrit aux patients souffrant de douleur chronique sévère. Le meilleur mode de délivrance pour les patients ayant développé une tolérance importante aux opioïdes est le timbre transdermique. Le problème est que les timbres usagés contiennent un résidu de fentanyl qui peut être extrait et réutilisé à mauvais escient, ce qui peut entraîner des conséquences graves. Pour y remédier, les patients à qui des timbres de fentanyl ont été prescrits en Ontario doivent rapporter les timbres utilisés pour recevoir les nouveaux, en vertu de la,/em> Loi pour protéger nos collectivités (politique d'échange de timbres, PET). Il s'agit d'un problème significatif en Ontario car cette province affiche le taux le plus élevé de prescription de fentanyl fortement dosé au Canada, avec 112 doses pour 1,000 habitants, alors pourtant que la prévalence de douleur chronique sévère est plus faible que dans les autres provinces (16,6% en Ontario contre 19,6 à 21,9%, d'après Gomes et al. 2014). L'objectif principal de la réforme est de rendre l'utilisation des timbres au fentanyl plus sûre et d'améliorer la sécurité pour les patients et la population en établissant un protocole d'élimination centralisé. La réforme s'inspire d'une initiative communautaire développée à North Bay, initiative approuvée par les collèges des professions de santé ainsi que par les communautés qui s'y sont volontairement associées avant même le vote de la Loi numéro 33. Les données préliminaires suggèrent que la politique PET est bien accueillie par les professionnels de santé, même si une évaluation est nécessaire pour mesurer l'efficacité de la politique en termes de réduction de la mes-utilisation et de l'abus des timbres au fentanyl.